Coping Strategies for Nurses’ Distress in Dealing with the COVID-19 Pandemic: A Scoping Review - Ika Nopa; L Meily Kurniawidjaja; Dadan Erwandi (Fakultas Ilmu Keperawatan Universitas Indonesia, 2024)
It is a well-known fact that the COVID-19 pandemic exacerbated the work stressors of nurses, which were already a problem previously, causing great distress. Hence, the need for effective coping strategies has been realized to prevent such distress, especially if a pandemic recurs. Determining how the types of coping strategies used by nurses impact their distress level in COVID-19 Pandemic. This review was conducted using the PRISMA Statement Recommendations Checklist and PRISMA—Extension for Scoping Reviews (PRISMA-SCR). The databases used were Willey Library, Science Direct, SCOPUS, and Springer Link for the literature search. Nurse and (“coping type” or “brief cope”) and COVID were the keywords used for search. The search was carried out using the following initial filters: “English and Indonesian,” language, and “free full text” availability. Only original research articles with a sample of nurses and a focus on coping with the COVID-19 pandemic were synthesized. The review contained 21 articles in total. In the Brief-COPE framework, an instrument designed to measure the types of coping strategies, there are several ways of classifying the types of coping strategies: based on outcome, engagement, stressor management goals, and source of support. The top coping strategies were acceptance, active coping, planning, religion, positive reframing, and seeking emotional support. Avoidance coping strategies significantly increase one’s depression and anxiety, while acceptance and positive reframing protect against anxiety and depression. This knowledge forms the basis of planning and designing a stress management program for dealing with extreme work stressors, such as pandemics. Future research should investigate how different types of stressors influence the use of coping strategies and distress in other situations. Keywords: coping type, COVID-19, distress, nurse Abstrak Strategi Mengatasi Distress Perawat dalam Menghadapi Pandemi COVID-19: A Scoping Review. Pandemi COVID-19 memperburuk stresor kerja perawat yang sebelumnya telah menjadi masalah. Koping yang efektif diperlukan untuk mempersiapkan manajemen stres dan mencegah distress jika pandemi terulang. Tinjauan ini bertujuan untuk mengetahui jenis koping yang digunakan perawat dalam menghadapi pandemi COVID-19 dan pengaruhnya terhadap distress. Tinjauan ini mengikuti panduan ceklis rekomendasi PRISMA, dan PRISMA—Extension for Scoping Reviews (PRISMA-ScR). Pencarian artikel dilakukan pada empat basis data yakni: SCOPUS, Science Direct, Springer Link, dan Willey Library. Nurse dan (“coping type” or “brief cope”) dan COVID adalah kata kunci yang digunakan untuk mencari literatur. Pencarian dibatasi pada artikel berbahasa Indonesia, Inggris, dan dapat diakses lengkap tidak berbayar. Artikel yang ditinjau terbatas pada artikel penelitian berfokus pada koping dalam menghadapi pandemi COVID-19 yang disintesis oleh penulis dengan perawat sebagai sampel. Sebanyak 21 artikel masuk dalam analisis. Terdapat beberapa cara untuk mengkategorikan jenis koping dalam kerangka Brief-COPE atau instrumen untuk mengukur jenis-jenis koping, yaitu berdasarkan hasil, keterlibatan, tujuan manajemen stres, dan sumber dukungan. Koping teratas yang digunakan perawat adalah penerimaan, koping aktif, perencanaan, agama, pembingkaian ulang positif, dan mencari dukungan emosional. Strategi koping avoidance secara signifikan dapat meningkatkan depresi dan kecemasan sedangkan penerimaan dan positive reframing dapat membentengi diri dari kecemasan dan depresi. Pengetahuan ini menjadi dasar perencanaan program manajemen stres untuk menghadapi stresor kerja ekstrem seperti pandemi. Penelitian di masa depan harus menyelidiki bagaimana berbagai jenis stresor memengaruhi penggunaan strategi koping dan distress dalam situasi lain. Kata Kunci: COVID-19, distress, jenis koping, perawat